Response: The Mobile Itineraries of Knowledge-scapes. Issue 1 (1st June 2019) - Sheller, Mimi
Abstract : This special section elucidates intersections between the historiography of mobilities and the interdisciplinary field of mobilities research. The articles highlight relationships between mobilities and stabilization, circulation and place-making, deterritorialization and reterritorialization. This response essay seeks to dispel three myths about mobility studies: (1) that it is purely about the contemporary world, rather than the historical dimensions of mobile processes; (2) that it focuses solely on material phenomenon of physical transport (i.e., of things and people) and ignores the movement of ideas, knowledge, and culture; and (3) that it is purely about "flows" and "circulation" and has little to teach us about friction, resistances, blockages, or uneven power relations. The most important intersections of the histories of mobilities and the field of mobility studies can be found in the ways in which each emphasizes power differentials, blockages, friction, and the relation between mobilities and immobilities.